The Impact of Sense of Community and Civic Engagement on the Well-Being of Student Executive Board Members of Politeknik Negeri Bandung - Maulana, Muhammad Yunus; Bakhrun, Akhmad (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2024)
AbstractHigher education institutions are expected to create environments that support positive growth, foster civic engagement, and enhance competencies. Hence, this study is examining the influence of sense of community and civic engagement as the antecedents of psychological aspect of student’s wellbeing. This research employs a quantitative approach using the SEM-PLS method. The questionnaire is completed by 53 respondents from a population of 222 of the Student Executive Board Members of Polban. The results show a significant difference in the influence of sense of community and civic engagement on students' wellbeing. This study presents a new evidence that a sense of community plays a crucial role in fostering civic engagement and student well-being, a connection that has not been previously explored in similar studies within the context of vocational higher education. However, civic engagement has minimal impact, direct or mediated. This study recommends that campuses prioritize community-building to enhance positive student development.—————AbstrakPerguruan tinggi diharapkan menjadi lingkungan yang mendukung pertumbuhan positif, bangkitnya keterlibatan warga negara serta peningkatan kompetensi sebagai calon profesional. Maka dari itu, penelitian ini menguji pengaruh rasa kebersamaan dan keterlibatan sipil sebagai anteseden dari aspek psikologis kesejahteraan mahasiswa. Penelitian menggunakan pendekatan kuantitatif dengan metode SEM-PLS. Kuesioner penelitian diisi oleh 53 orang sampel dari populasi berjumlah 222 orang pengurus dan anggota BEM Polban kabinet Pilar Impresif. Hasil analisis menampikan adanya signifikansi yang berbeda antara rasa kebersamaan dan keterlibatan sipil terhadap kesejahteraan mahasiswa. Penelitian ini menunjukan bukti baru bahwa rasa memiliki berperan penting dalam mendorong keterlibatan sipil dan kesejahteraan mahasiswa yang belum pernah diungkap dalam kajian serupa pada konteks pendidikan di perguruan tinggi vokasi. Adapun, pengaruh keterlibatan sipil, baik secara langusng maupun sebagai mediator rasa memiliki terhadap kesejahteraan mahasiswa, hasilnya ternyata tidak signifikan. Hasil kajian ini menunjukan bahwa arah kebijakan perlu memprioritaskan internalisasi aspek rasa kebersamaan secara efektif terhadap perkembangan positif mahasiswa.